Monitoring and feeding integration of demand feeder systems - Mohd Razman, Mohd Azraai; Abdul Majeed, Anwar P.P.; Musa, Rabiu Muazu; Taha, Zahari; Susto, Gian-Antonio; Mukai, Yukinori (Springer, 2020)
This chapter highlights the findings of the developmental monitoring systems for swimming pattern or motion analysis with regard to feeding behaviour. A benchmark for examining the framework on how scientists control fish in animal variable function factors was gathered and referred to gauge the adequate design in constructing a viable device. The validation of image processing and automated demand feeder to determine the results will also be considered, as a validation aspect between the system of tracking and the behaviour of the Lates calcarifer where the pixel intensity will be extracted as the features. The results of this chapter will enable the reader on the development of an integrated feeder scheme that consolidates surveillance scheme to identify the feeding behaviour and relation towards the specific growth rate (SGR).